Optimalisasi Pengelolaan Dan Pemanfaatan Tempat Pengolahan Sampah Reduce-Reuse-Recycle (TPS3R) Desa Rajik, Kec. Simpangrimba, Kabupaten Bangka Selatan - Mursyid Hasan Basri; Indah Noviyanti; Sumar Sumar (Community Engagement and Emergence Journal (CEEJ), 2025)
This community service program aims to optimize the management and utilization of the Reduce-Reuse-Recycle Waste Processing Site (TPS3R) in Rajik Village, Simpang Rimba District, South Bangka Regency. The main problems identified are the low operational effectiveness of the TPS3R facility and the limited community participation in sorting and managing waste. This condition has led to the accumulation of household waste, the decline of environmental quality, and the absence of a well-structured waste management system at the village level. The program was carried out through a scientific study and participatory action using a mixed-methods approach, combining quantitative surveys and qualitative interviews to obtain a comprehensive understanding of waste management conditions in Rajik Village. Through this approach, socialization, training, and mediation activities were conducted, involving community members, village officials, and TPS3R managers. The results indicate a significant improvement in community awareness and participation in waste management following a series of outreach and training sessions. Residents have begun to understand the importance of the 3R-based waste management system and have shown commitment to practicing waste sorting and recycling at the household level. Moreover, the program encouraged the development of creative economic awareness based on waste management, where the community started to recognize the economic potential of recyclable products. Overall, this program successfully strengthened collaboration among the village government, TPS3R management, and the local community in realizing a self-reliant, participatory, and sustainable waste management system, while making a tangible contribution to building a cleaner and more productive village environment.